Wątki patriotyczne dotyczące wychowania rodzinnego w prasie górnośląskiej przełomu XIX i XX wieku (na przykładzie wybranych czasopism) - Wilczek, Wioletta (Forum Lingwistyczne, 2019)
The article concerns patriotic threads in the Upper Silesian press concerning the upbringing of children at the turn of the 19th and 20th centuries. The subject of the description are the magazines “Rodzina” and “Katolik” from the years 1890–1918. The analysis included the observed elements of upbringing constituting components of patriotism: cultivation of the mother tongue, love for the homeland, memory of history, appreciation of acts of heroism, readiness to sacrifice for the country as well as cultivation of the system of values. The background for the considerations was the historical reality, reflected in the presented content. The basis of the description was the linguistic image of the world and the category of evaluation, which made it possible to indicate the scope of linguistic elements of patriotic upbringing.